PC to PC communication via public telephone network to perform a task from a distant location - 431482 Lee, Su Wen (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2003